2008
DOI: 10.1121/1.2998980
|View full text |Cite
|
Sign up to set email alerts
|

Listening to every other word: Examining the strength of linkage variables in forming streams of speech

Abstract: In a variation on a procedure originally developed by Broadbent ͓͑1952͒. "Failures of attention in selective listening," J. Exp. Psychol. 44, 428-433͔ listeners were presented with two sentences spoken in a sequential, interleaved-word format. Sentence one ͑target͒ comprised the odd-numbered words in the sequence and sentence two ͑masker͒ comprised the even-numbered words in the sequence. The task was to report the words in sentence one. The goal was to determine the effectiveness of cues linking the words of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 26 publications
2
103
1
Order By: Relevance
“…Because the words were spoken individually with neutral inflection when recorded (cf. Kidd et al, 2008b), it also is possible that less of a benefit of voice was found here than would occur for natural speech where coarticulation and intonation patterns may provide cues linking words together. Furthermore, the familiarity of the talkers was not assessed or explicitly manipulated and that factor has been shown to exert an influence on the ability to selectively attend to one talker among competing talkers (e.g., Newman and Evers, 2007;Johnsrude et al, 2013).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Because the words were spoken individually with neutral inflection when recorded (cf. Kidd et al, 2008b), it also is possible that less of a benefit of voice was found here than would occur for natural speech where coarticulation and intonation patterns may provide cues linking words together. Furthermore, the familiarity of the talkers was not assessed or explicitly manipulated and that factor has been shown to exert an influence on the ability to selectively attend to one talker among competing talkers (e.g., Newman and Evers, 2007;Johnsrude et al, 2013).…”
Section: Discussionmentioning
confidence: 64%
“…Significant differences were found for identification performance when the target word syntax varied (as here, better performance for correct syntax) but masker syntax was not a significant factor. There were many differences between the present study, the Kidd et al (2008b) study, and the Brouwer et al (2012) study with respect to the methods that were used. Perhaps most importantly, though, Brouwer et al employed semantically more meaningful target utterances than the other two studies.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations